2016
DOI: 10.1055/s-0042-108340
|View full text |Cite
|
Sign up to set email alerts
|

The Metabolic Plant Feedback Hypothesis: How Plant Secondary Metabolites Nonspecifically Impact Human Health

Abstract: Humans can ingest gram amounts of plant secondary metabolites daily through diet. Many of these phytochemicals are bioactive beyond our current understanding because they act through weak negative biological feedback mechanisms, undetectable in vitro. Homeostatic-type assessments shed light on the evolutionary implications of the human diet from plants, giving rise to the metabolic plant feedback hypothesis. The hypothesis states that ancient diets rich in carbohydrates coincide with bulk dietary phytochemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 117 publications
(127 reference statements)
0
11
0
Order By: Relevance
“…Nevertheless, chemical diversity in plants is shaped by environmental conditions and predation pressure, leading to vitamin‐like (i.e. essential), nonspecific (Gertsch, ) or even xenohormetic secondary metabolites (Lamming et al ., ; Howitz and Sinclair, ) in the Animalia food pyramid. Neurotransmitters, modulators and hormones naturally have very short half‐lives and are not generally orally bioavailable due to the metabolic enzymes present in most tissues, including the GI tract.…”
Section: Cannabimimetics In the Plant Kingdom And Vegetable Foodmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, chemical diversity in plants is shaped by environmental conditions and predation pressure, leading to vitamin‐like (i.e. essential), nonspecific (Gertsch, ) or even xenohormetic secondary metabolites (Lamming et al ., ; Howitz and Sinclair, ) in the Animalia food pyramid. Neurotransmitters, modulators and hormones naturally have very short half‐lives and are not generally orally bioavailable due to the metabolic enzymes present in most tissues, including the GI tract.…”
Section: Cannabimimetics In the Plant Kingdom And Vegetable Foodmentioning
confidence: 99%
“…There is compelling evidence that numerous vegetables and spices exert beneficial effects in the context of obesity, the metabolic syndrome and diabetes (Leiherer et al ., ). There could even be a diet‐mediated metabolic plant feedback beyond nutrients and vitamins (Gertsch, ). Diet is important for the development of the immune system, stress axis and neurobiological fitness in infants, and the ECS appears to play a critical role in this process (Harrison and Baune, ; Moretti et al ., ).…”
Section: Prospects For Nutraceutical Research?mentioning
confidence: 99%
See 1 more Smart Citation
“…Medical and nutritional research has for decades, emphasized the health benefits of consuming fruits and their role in the management/ prevention of chronic diseases/conditions such as cardiovascular disease, certain cancers, type II diabetes mellitus, obesity, chronic kidney disease, chronic lung disease, chronic obstructive pulmonary disease etc 3 . Further, the World Health Organization estimation data has revealed that, approximately 1.7 million (2.8%) deaths from diet related chronic diseases per annum are linked with low consumption of fruits and vegetables 2 .The importance of consumption of fruits and their involvement in the protection of cells from oxidative stress has become a debatable topic in this era 4 . In particular, phytochemicals with antioxidant potential are wellreported to play a role in reducing the consequences of oxidative stress in disease development and in aging process, thus contribute to overall health-protective effects 5 .…”
Section: Introductionmentioning
confidence: 99%
“…For the great majority of medicinal plants, the underlying molecular mechanisms of action remain unknown, thus holding a promise for drug discovery [4]. From an evolutionary point of view, most plant secondary metabolites might be weak nonspecific modulators of mammalian proteins via our diet and execute chronic health benefits [5]. Like most medicines, botanical drugs can trigger placebo effects and thus represent ancient symbols of a meaning response (vide in-Med Cannabis Cannabinoids 2018;1:60-64 DOI: 10.1159/000489291 fra), a term coined by Moerman and Jonas [6].…”
mentioning
confidence: 99%